Case Report: Successful Management of a Refractory Plasmablastic Lymphoma Patient With Tislelizumab and Lenalidomide - Cheng, Lili; Song, Qi; Liu, Mengke; Wang, Yan; Yi, Hongmei; Qian, Ying; Xu, Pengpeng; Cheng, Shu; Wang, Chaofu; Wang, Li; Zhao, Weili (Frontiers in Immunology, 2021)
Plasmablastic lymphoma (PBL) is a rare and aggressive hematological malignancy. PBL commonly occurs in immune incompetent patients, such as those with human immunodeficiency virus (HIV), post-transplant status, or immunosenescence. Given its rarity, there is no specific standard treatment for PBL. However, small case series have shown that intensive chemotherapies combined with anti-myeloma agents such as bortezomib and lenalidomide were effective in treating PBL. Unfortunately, some fragile patients could not tolerate intensive chemotherapeutic regimens, especially the elderly patients. Here we presented a 76-year-old female PBL patient refractory to miniCHOP regimen combined with bortezomib but achieved complete remission when treated with tislelizumab combined with lenalidomide, indicating that immune therapy may be a potential treatment for PBL. To our knowledge, this is the first chemoresistant PBL patient that has been successfully treated with checkpoint inhibitor plus lenalidomide, thus providing new insight towards PBL management.